Association of sequence polymorphism in the mitochondrial D-loop with chronic kidney disease. (June 2014) - Bai, Yaling; Guo, Zhanjun; Xu, Jinsheng; Zhang, Junxia; Cui, Liwen; Zhang, Huiran; Zhang, Shenglei; Ai, Xiaolu
Abstract Background: The mitochondrial displacement loop (D-loop) is known to accumulate mutations and single nucleotide polymorphisms (SNPs) at a higher frequency than other regions of mitochondrial DNA (mtDNA). Methods: This is a case–control study. We sequenced SNPs in the D-loop of mtDNA and investigated their association with the risk of chronic kidney disease (CKD). Results: A total of 144 SNPs referring to the positions of the Revised Cambridge Reference Sequence (rCRS) for mitochondrial genome were identified in a case–control study. The minor alleles of nucleotides 73G, 146C, 150T, 194T, 195C and 310C were associated with an increased risk for CKD patients. Conclusion: Analysis of genetic polymorphisms in the mitochondrial D-loop can help identify the people who are at a high risk of developing chronic kidney disease. These SNPs can be considered as potential predictors for CKD.